Activation of SIRT-1 Pathway by Nanoceria Sheds Light on Its Ameliorative Effect on Doxorubicin-Induced Cognitive Impairment (Chemobrain): Restraining Its Neuroinflammation, Synaptic Dysplasticity and Apoptosis - Medhat Taha; Sara T. Elazab; Alaa. M. Badawy; Abdullah A. Saati; Naeem F. Qusty; Abdullah G. Al-Kushi; Anas Sarhan; Amira Osman; Amira E. Farage (MDPI AG, 2022)
Chemo fog is one of the most serious health concerns encountered by cancer survivors receiving doxorubicin (DOX)-based chemotherapy. Oxidative stress, neuroinflammation, apoptosis and impairment of synaptic plasticity are regarded as the key factors implicated in DOX-induced cognitive impairment. This research aimed to assess the possible neuroprotective effect of cerium oxide nanoparticles (CeNPs) against DOX-induced neurotoxicity. Forty-eight rats were divided into four groups (12 rats/group): control group, CeNPs group (received oral CeNPs solution (35 mg/kg) daily for 4 weeks), and DOX group (were administered DOX intraperitoneally (2 mg/kg, once/week for 4 weeks)) and DOX+ CeNPs group. The findings revealed that CeNPs mitigated behavioral alterations in DOX-induced cognitive deficit. Additionally, CeNPs alleviated the histopathological abnormalities in hippocampus and ameliorated DOX-induced neuroinflammation by downregulating the expression of NF-κB, TNF-α, IL-1β and IL6. In addition, CeNPs antagonized the apoptosis through reducing the protein expression of cytochrome c and caspase 3. In addition, it stimulated the antioxidant defense, as indicated by upregulating the expression of the Nrf2, HO-1 and PGC-1α genes. CeNPs improved synaptic plasticity via acting on the BDNF. These actions were related through the modification of SIRT-1 expression. Based on the aforementioned results, CeNPs antagonized the doxorubicin-induced neurodegeneration by its antioxidant, anti-inflammatory and antiapoptotic effects, alongside its SIRT-1 mediated mechanisms.